Increasing forest loss worldwide from invasive pests requires new trade regulations. Issue 8 (15th September 2014) - Roy, Bitty A; Alexander, Helen M; Davidson, Jennifer; Campbell, Faith T; Burdon, Jeremy J; Sniezko, Richard; Brasier, Clive
Abstract : Loss of forests due to non‐native invasive pests (including insects, nematodes, and pathogens) is a global phenomenon with profound population, community, ecosystem, and economic impacts. We review the magnitude of pest‐associated forest loss worldwide and discuss the major ecological and evolutionary causes and consequences of these invasions. After compiling and analyzing a dataset of pest invasions from 21 countries, we show that the number of forest pest invasions recorded for a given country has a significant positive relationship with trade (as indicated by gross domestic product) and is not associated with the amount of forested land within that country. We recommend revisions to existing international protocols for preventing pest entry and proliferation, including prohibiting shipments of non‐essential plants and plant products unless quarantined. Because invasions often originate from taxa that are scientifically described only after their introduction, current phytosanitary regulations – which target specific, already named organisms – are ineffective.